Voices from the margins: amplifying the workplace realities of black child-free women in South Africa - Acheampong, Nadine Borkor (Organisational Psychology, 2025)
The rising number of individuals identifying as child-free has sparked a growing interest in understanding this demographic's unique challenges and opportunities. Despite progress in South Africa's equality legislation, child-free black women remain marginalised, frequently confronting stereotypes and assumptions that challenge both their personal and professional identities. This study explores these specific dynamics through semi-structured, in-depth interviews with 22 child-free black women in South Africa, exploring how ‘race', ‘gender', and ‘child-free' status intersect to shape their workplace experiences. All women were formally employed and resided in South Africa, identifying as black, and between the ages of 24 – 38, with at least two years of full-time working experience. Through an intersectional lens and the application of role theory, this paper provides a nuanced perspective on how child-free individuals navigate and negotiate their roles and identities. Thematic analysis was employed to explore the data, delving into participant's insights and perspectives to gain a thorough understanding of their lived realities. The study's findings revealed the opportunities and challenges faced by child-free black women in their workplace. Three key themes emerged that reflected child-free black women's lived experiences in the South African workplace: (1) The availability paradox: navigating time and identity in child-free lives, (2) Redefining family at work: child-free identities within organisational norms, (3) Unseen needs: fostering inclusive spaces for child-free workers. Through these findings, recommendations for improving workplace support for child-free black women are presented.